Soil quality indicators of integrated rice-crayfish farming in the Jianghan Plain, China using a minimum data set - Yuan, Pengli; Wang, Jinping; Li, Chengfang; Xiao, Qiuqing; Liu, Qingjun; Sun, Zichuan; Wang, Jinhua; Cao, Cougui (Soil & tillage research, 2020)
•This study compared soil quality indices based on a set of 12 indicators.•Soil quality index was developed using SOC, MBC, TK, Eh, and Mn(II).•Mn(II) was the dominant soil quality factor, contributing 34.24 % to the SQI value and represents the redox state of the soil.•This study is beneficial for implementing rice-crayfish practices and management of rice planting areas. In order to employ appropriate management measures for rice-crayfish farming systems in the Jianghan Plain, it is critical to evaluate how this process affects the soil quality. By taking 76 soil samples from three different crayfish aquaculture periods (≥10 years (Y10), 4-6 years (Y4), and 1–2 years (Y1)) from paddy fields and using traditional rice planting patterns as controls (rice-wheat, rice-grape, and rice monoculture as CK), we surveyed the influence of different years of rice-crayfish development in rice fields on the soil quality using an integrated soil quality index (SQI). The results showed that crayfish aquaculture significantly affected the soil quality of the paddy fields. The SQI assessed the soil organic carbon (SOC), microbial biomass carbon (MBC), total potassium (TK), oxidation-reduction potential (Eh), and Mn(II). The highest SQI values were detected in the Y10 rice-crayfish system, and the lowest in the traditional paddy field. Mn(II) was the dominant soil quality factor, contributing 34.24 % to the SQI value. The relativity analysis also demonstrated that the SQI values were inversely correlated with Mn(II), and this may be used as a characteristic indicator to evaluate the soil quality of rice-crayfish systems in paddy fields. Overall, crayfish aquaculture in rice fields significantly improved the soil quality. The findings of this research showed that the use of a minimum data set (MDS), the SQI, is a potent means for assessing the soil quality of rice-crayfish systems.